Affixation of Taro Dialect: A Descriptive Study - Artawan, Kadek (Universitas Pendidikan Ganesha, 2018)
This descriptive study aimed at describing the number of prefixes and suffixes in Taro Dialect and its types of inflectional and derivational. This study is a descriptive qualitative research. Two informant samples of Taro Dialect were chosen based on a set of criteria. The data were collected based on three techniques, namely; observation, recording technique, and interview (listening and noting) technique. The results of the study show that there were five prefixes and five suffixes existing in Taro Dialect. The prefixes were N-, ma-, sa-, pa-, and ka-. The suffixes were -in, -ne, -an, -ang, and -e. The prefixes and suffixes that belong to derivation are: prefix N-, ma-, sa-, pa, and ka- and suffix -ang, an, -ne, and -in. The prefixes and suffixes that belong to inflection are: prefixes N-, ma-, and ka- and suffix -ang, an, -ne, -in, and -e.